Range distribution and contributions to taxonomy of Elops smithi (ELOPIFORMES: ELOPIDAE) - SOUSA, RODRIGO P.C. DE; SODRÉ, DENISE; COSTA, RAUQUÍRIO M. DA; VALLINOTO, MARCELO; OLIVEIRA, EDIVALDO H.C.; SILVA-OLIVEIRA, GLÁUCIA C.; SAMPAIO, IRACILDA; GUIMARÃES-COSTA, AURYCÉIA (Anais da Academia Brasileira de Ciências, 2019)
This study presents the first record of Elops smithi for northern Brazil. The evidence suggests this species is being misidentified incorrectly as Elops saurus in estuaries of the Western Atlantic Ocean. Here, morphological, molecular, and cytogenetic ﻿evidence identified all ladyfish specimens from one estuary in the region as E. smithi. ﻿Thus, at least Elops smithi occurs in the northern coast of Brazil and it is recommended that specimens from this region identified as E. saurus be further investigated with genetic and cytogenetic tools in order to assure a correct species identification.